Pengembangan Media Roka'at (Roda Akar dan Pangkat) untuk Meningkatkan Kemampuan Reversible Thinking Matematis Siswa - Rohim, Abdur; Asmana, Aresqi Tunggal (MAJAMATH: Jurnal Matematika dan Pendidikan Matematika, 2023)
Students with high reversible thinking abilities find it easier to find solutions to math problems. This is because the ability is reversible, requiring students to rethink answers that have been taken in other ways. Thus, minimizing the chances of error from every solution they get. One way to bring up this ability is to provide a medium when learning takes place. The reality in the field is that there is no media used to improve reversible thinking abilities in root and rank material. ROKA'AT media (Wheel of Roots and Ranks) is one of the media that can be developed that teaches the concept of reversibility. This research includes research on the development of learning media which has the goal of increasing reversible thinking abilities. There are 3 stages of this development, namely the preliminary stage, development and evaluation. Based on the validation results, it was found that ROKA'AT media met valid criteria with an overall percentage of media experts of 93.68% and practitioners of 100%, so the media was suitable for testing. After being tested, it was obtained that the practicality criteria met 96.84% in the very practical category. The pretest and posttest results show which means that ROKA'AT media is effective in improving students' reversible mathematical thinking abilities.